Annotated catalogue of Enicocephalomorpha, Dipsocoromorpha, Nepomorpha, Gerromorpha, and Leptopodomorpha (Hemiptera: Heteroptera) of Turkey, with new records - Fent, Meral; Kment, Petr; Çamur-Eli̇pek Belgi̇n; Kirgiz Ti̇mur (Zootaxa, 2011)
An annotated check-list of the aquatic and semi-aquatic bugs of the infraorders Enicocephalomorpha, Dipsocoromorpha, Nepomorpha, Gerromorpha, and Leptopodomorpha of Turkey and its geographical parts (Turkish Thrace [i.e., European Turkey] and Anatolia [i.e., the Asian Turkey]) is presented. The nomenclatoric history of Alpagut Kıyak, 1995 (= Harpago Linnavuori, 1951, = Raunocoris Baena & Alonso-Zarazaga, 2009) is reviewed, its gender is fixed, and two new combinations are proposed: Alpagut maroccanus (Wagner, 1960) comb. nov., and Alpagut medius (Rey, 1888) comb. nov. The list is based on a survey of all published records as well as on examination of collection material, including recent material collected in the poorly explored Turkish Thrace. The following numbers of species are accepted as occurring in Turkey: Enicocephalomorpha—1 species (Asian Turkey only), Dipsocoromorpha—2 species (Asian Turkey only), Nepomorpha—49 species (29 in European and 47 in Asian Turkey), Gerromorpha—27 species (10 in European and 25 in Asian Turkey), and Leptopodomorpha—21 species (6 in European and 20 in Asian Turkey). Forty species are known from both European and Asian Turkey, whereas 5 are recorded only from European Turkey and 55 only from Asian Turkey. Eight species and subspecies, Micronecta scholtzi (Fieber, 1860), Hesperocorixa sahlbergi (Fieber, 1848), Sigara iranica Lindberg, 1964, Hebrus ruficeps Thomson, 1871, Velia affinis filippii Tamanini, 1947, Velia rhadamantha rhadamantha Hoberlandt, 1941, Gerris kabaishanus Linnavuori, 1998, and Saldula pilosella pilosella (Thomson, 1871), are reported from Turkey for the first time; and four species, Sigara scripta (Rambur, 1840), Corixa punctata (Illiger, 1807), C. panzeri (Fieber, 1848), and Gerris argentatus Schummel, 1832, are new records for Turkish Thrace. First exact localities of several other species are provided as well. Three species, Sigara kervillei (Poisson, 1927), Microvelia hozari Hoberlandt, 1952, and Velia mariae Tamanini, 1971, seem to be endemic to Anatolia; 22 species occur only in Turkey and the adjacent regions (Balkan Peninsula, Cyprus, Near East, Iran, and Transcaucasia). The 75 remaining species have a wider distribution. Occurrences of 10 species, previously recorded from Turkey, need further confirmation. Finally, 19 species-group taxa are excluded from Turkish fauna as they are based on proven or suspected misidentifications or taxonomic confusion: Micronecta minutissima (Linnaeus, 1758), Cymatia bonsdorffii (C. R. Sahlberg, 1819), Arctocorisa carinata carinata (C. R. Sahlberg, 1819), Callicorixa praeusta praeusta (Fieber, 1848), Hesperocorixa castanea (Thomson, 1869), Hesperocorixa occulta (Lundblad, 1929), Sigara hoggarica Poisson, 1929, Sigara scotti (Douglas & Scott, 1868), Heleocoris minusculus (Walker, 1870), Anisops debilis canariensis Noualhier, 1893, Velia caprai caprai Tamanini, 1947, Aquarius najas (De Geer, 1773), Gerris costae costae (Herrich-Schaeffer, 1850), G. gibbifer Schummel, 1832, G. lateralis Schummel, 1832, Saldula fucicola (Sahlberg, 1870), S. pilosella hirsuta (Reuter, 1888), Salda morio Zetterstedt, 1838, and S. muelleri (Gmelin, 1790). In addition, first records of Aquarius ventralis (Fieber, 1860) from Syria, and Saldula melanoscela (Fieber, 1859) and Leptopus marmoratus (Goeze, 1778) from Lebanon, are provided. The previously published records of Rhagovelia nigricans nigricans (Burmeister, 1835) from Cyprus and Israel (Hoberlandt 1952b) belong to R. infernalis africana Lundblad, 1936.